A justa causa na formação preliminar da culpa no processo penal: Lei 12830/13 e a fundamentação do indiciamento no inquérito policial como direito fundamental - Lima, Ernando Bezerra De Oliveira (2016)
The debate about the preliminary formation of guilt in criminal proceedings, taking, therefore, as a reference the institute of indictment in police investigation, is inserted into an argument even more comprehensive and relevant, bringing the perspective of a fundamental right of a suspect to a motivated indictment as the main topic. The indictment is known as a necessary procediment act in the whole process; because it implicates to harmful consequences to the person under the investigation, in some cases it results the withdraw of public roles, among other situations. It's also known as an administrative act, brought by the constitutional law that states it deserves proper foundation. Thus, the reasoning in criminal proceedings receives a peculiar nomenclature: just cause. This expression is routinely handled in the criminal proceedings as designating the recognized need for sufficient motivation for begining the police investigation and the offer and receipt of the complaint or claim, for the establishment of criminal prosecution. From the enactment of Law 12830/13, the indictment in the police investigation has gained more notoriety and rejoined the debate in the national legal scenario, especially because it is one of the most significant requirements set out in this legislation. So with this Law 12830/13 it snows that in another moment of criminal investigation it is essential the presence of just cause. So it turns out, even in poor analysis, that that piece of legislation, despite the suggestion doctrinal and jurisprudential requirement, inaugurated a true moment of preliminary training of guilt in the Brazilian criminal proceedings. From the opinions of the doctrine and the jurisprudential positions, we could see the demand in this direction, although there was no written regulation that obligated. It should be noted that the legal requirements outlined in this law do not seem new in the regulatory context, doctrinal and jurisprudential national rights, since it has inspired constitutional designations, but they are presented, from then on, as impositions reinforced in the face of normativity cogent own legislative document.